2009
DOI: 10.1080/13813450902887055
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte inflammation model for cytotoxicity research: fructose or glycolaldehyde as a source of endogenous toxins

Abstract: Insulin resistance and hepatotoxicity induced in high fructose fed rats may involve fructose derived endogenous toxins formed by inflammation. Thus fructose was seventy-fold more toxic if hepatocytes were exposed to non-toxic levels of hydrogen peroxide (H(2)O(2)) released by inflammatory cells. This was prevented by iron (Fe) chelators, hydroxyl radical scavengers, and increased by Fe, copper (Cu) or catalase inhibition. Fructose or glyceraldehyde/dihydroxyacetone metabolites were oxidized by Fenton radicals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Table 4 Protective effects of ferulic acid and related polyphenols on GO-or MGO-induced cytotoxicity, ROS formation, MMP, and protein carbonylation in GSH-depleted hepatocytes. Previously, our laboratory showed that H 2 O 2 markedly increased fructose [15] or GO or MGO-induced cytotoxicity [3]. The model was used in the current study to investigate whether the polyphenols could protect GO-or MGO-induced cytotoxicity and oxidative stress.…”
Section: Preventing Go-or Mgo-induced Cytotoxicity and Oxidative Strementioning
confidence: 99%
See 1 more Smart Citation
“…Table 4 Protective effects of ferulic acid and related polyphenols on GO-or MGO-induced cytotoxicity, ROS formation, MMP, and protein carbonylation in GSH-depleted hepatocytes. Previously, our laboratory showed that H 2 O 2 markedly increased fructose [15] or GO or MGO-induced cytotoxicity [3]. The model was used in the current study to investigate whether the polyphenols could protect GO-or MGO-induced cytotoxicity and oxidative stress.…”
Section: Preventing Go-or Mgo-induced Cytotoxicity and Oxidative Strementioning
confidence: 99%
“…Additional hydrogen peroxide (H 2 O 2 ) from either endogenous catalase inhibition or from an exogenous source such as glucose/glucose oxidase (a non-toxic H 2 O 2 generating system) increased GO formation from glycolaldehyde and also promoted radical formation from GO and possibly from MGO [3]. Our laboratory previously demonstrated that fructose-induced hepatotoxicity increased more than 100-fold in the presence of a non-toxic concentration of H 2 O 2 so as to mimic H 2 O 2 levels formed by NADPH oxidase (NOX) released by activated immune cells such as neutrophils, eosinophils, and macrophages during an acute episode of inflammation [15,16]. The increased hepatotoxicity was mainly due to the enhanced conversion of fructose and fructose metabolites to form GO which could produce reactive radicals leading to increased ROS formation [1].…”
Section: Introductionmentioning
confidence: 95%
“…In the present study, we used GA as an AGE precursor to accumulate AGE intracellularly and to demonstrate that accumulation of intracellular AGEs induces apoptosis in chondrocytes. It has been shown that GA carbonylate rat liver cell or human breast carcinoma cell, thereby inducing apoptosis . Other studies have shown that other AGE precursors such as methylglyoxal or glyceraldehyde also cause apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…The fructose transporter GLUT5 receptors are expressed on the cancer cells like colorectal and breast cancers indicated that fructose can be used as fuel by several types of cancers [153,154]. Excessive intake of fructose can lead to increased formation of RDS production via formation of glycolaldehyde [155]. Glyoxal is an autoxidation product during fructose metabolism and also a contaminant in the food processing promoted intestinal tumor growth in mouse model.…”
Section: Cancermentioning
confidence: 99%